What Have We Learned from a Decade of Manufacturing Enterprise Surveys in Africa? - Bigsten, Arne; Söderbom, Måns (Oxford University Press on behalf of the World Bank, 2013)
In the early 1990s the World Bank launched the Regional Program on Enterprise Development (RPED) in several African countries, a key component of which was to collect data on manufacturing firms. The data sets built by these and subsequent enterprise surveys in Africa generated considerable research. This article surveys the research on the African business environment, focusing on risk, access to credit, labor, and infrastructure, and on how firms organize themselves and do business. It reviews the research on enterprise performance, including enterprise growth, investment, and exports. The article concludes with a discussion of policy lessons.